Analisis Ketimpangan Pembangunan dan Pertumbuhan Ekonomi Antar Wilayah Kabupaten/Kota di Provinsi Papua Tahun 2018-2021 (Analysis of Development Inequality and Economic Growth Between Regions Regency/City in Papua Province 2018-2021) - Eiron Wenda; Jane Tambas; Leonardus R. Rengkung (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The economic development of the Papua Province has begun to be seen with the development of several regional potentials. However, these favorable conditions do not make the economic development of each Regency/City more evenly distributed. For this reason, research on inequality in development between districts in Papua Province is very necessary. Furthermore, the objective of this study is to analyze the level of development inequality and economic growth between districts/cities in Papua Province in 2018-2021. This research was conducted from November 2021 to February 2022. The data used are secondary data from the Central Statistics Agency (BPS) of Papua Province; with the variables used: GRDP of Papua Province at Constant Prices, GRDP of Regency/City of Papua Province, Total Population of Papua Province, and Total Population of Regency/City of Papua Province. Analysis of the data used in this study is the analysis of regional inequality (Williamson Index) and analysis of the regional approach (Klassen Typology) with processing using Microsoft Excel. Based on the results of the research and discussion, the conclusions of this study are that: inequality that occurs in Papua Province between districts/cities in the 2018-2021 period had increased. The average Williamson Index score in Papua Province in the research period was 0.585256472 (or 0.59) with high inequality criteria. And, the classification of districts/cities based on economic growth and per capita GRDP in Papua Province uses the Klassen Typology analysis tool for the 2018-2021 period with a regional approach divided into four existing classifications. Developed and fast-growing regions, namely Merauke, Sarmi, Boven Digoel, Bintang Mountains, Nabire, Keerom, Supiori, Waropen, and Jayapura Regencies; developed but depressed areas, namely Kota Jayapura, Mamberamo Raya, and Mimika; areas developing fast but not developing, namely Puncak, Mappi, Biak Numfor, Central Mamberamo, Nduga, Lanny Jaya, Dogiyai, and the Yapen Islands; and relatively underdeveloped areas, namely Paniai, Jayawijaya, Deiyai, Yalimo, Tolikara, Puncak Jaya, Yahukimo, and Intan Jaya.